2022
DOI: 10.1002/jmri.28372
|View full text |Cite
|
Sign up to set email alerts
|

Prospective of 31P MR Spectroscopy in Hepatopancreatobiliary Cancer: A Systematic Review of the Literature

Abstract: Background: The incidence of liver and pancreatic cancer is rising. Patients benefit from current treatments, but there are limitations in the evaluation of (early) response to treatment. Tumor metabolic alterations can be measured noninvasively with phosphorus ( 31 P) magnetic resonance spectroscopy (MRS). Purpose: To conduct a quantitative analysis of the available literature on 31 P MRS performed in hepatopancreatobiliary cancer and to provide insight into its current and potential for therapy (non-) respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…As a result, the PME/PDE ratio showed more variable changes and was only elevated in the liver metastases of patient 1, but not in patient 2. In previous studies of 31 P MRS in liver cancer, elevated PME/ATP (34%-200%), PME/PDE (2%-267%), and PME/Pi (21%-233%) ratios were found in liver tumors compared with healthy liver tissue (reviewed in 26 ). The heterogeneous results may be related to the different etiologies of liver tumors (e.g., primary origin or liver metastasis of colorectal cancer) included in these studies, but are largely in agreement with the elevated PMEs observed in the metastases from the current study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a result, the PME/PDE ratio showed more variable changes and was only elevated in the liver metastases of patient 1, but not in patient 2. In previous studies of 31 P MRS in liver cancer, elevated PME/ATP (34%-200%), PME/PDE (2%-267%), and PME/Pi (21%-233%) ratios were found in liver tumors compared with healthy liver tissue (reviewed in 26 ). The heterogeneous results may be related to the different etiologies of liver tumors (e.g., primary origin or liver metastasis of colorectal cancer) included in these studies, but are largely in agreement with the elevated PMEs observed in the metastases from the current study.…”
Section: Discussionmentioning
confidence: 95%
“…The application of 31 P MRS in liver tumors has recently been reviewed 26 . 31 P MRS of liver tumors has been performed at magnetic field strengths of 1.5 and 3 T and, because of the low intrinsic sensitivity of 31 P MRS, rather large voxel sizes have been used (up to 560 mL).…”
Section: Introductionmentioning
confidence: 99%
“…fMRI, indicating brain activity through blood flow, offers high sensitivity (80%–90%) and specificity in identifying key brain areas but is susceptible to motion artifacts and variable interpretation ( 22 ). MRS provides a window into the biochemical makeup of tissues, yielding crucial data on tumor metabolism and types ( 23 ). Each modality contributes uniquely to tumor diagnosis, balancing specific advantages and inherent challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, the method has also been used to study neurological disorders [ 57 , 58 ]. 31 P MRS has potential for use in studies in hepatopancreatobiliary cancer [ 59 ].…”
Section: The Physical Phenomenon Of Magnetic Resonancementioning
confidence: 99%